INDUKSIVARIASI SOMAKLONAL JARAK PAGAR (JATROPHA CURCAS L.) UNTUK MENDAPATKAN KARAKTERTOLERAN CEKAMAN KEKERINGAN - Maftuchah . (Jurnal Gamma, 2010)
Experimental activities is conduct in several stages, that is : somaclonal variation induction incastor oil in vitro culture through the use of PEG and selected plantlet is reproduce in vitro. In vitroselection procedure is done by planting cotyledon explants from castor oil seedlings age 10-14 daysin nutrient medium MS+BAP+IBA. Seed sterilization is done using Tween 20, Benlate, 90% alcohol,50% chloroc and sterile water.After callus is grown, callus will be sub-cultured into nutrient mediumMS+BAP with PEG addition. Selected callus will be transferred into nutrient medium MS + potassiumpantotenat + active coal until it shows root growth.Result of experiment has shown that the higher PEG concentration will suppress thegrowth of castor oil callus. In PEG concentration 15% the mortality rate of castor oil callus (LD) is64,29% and for PEG concentration 20% the mortality rate of castor oil callus is 92,86%. For thenext phase is in vitro selection process through treatment of 15% PEG toward all seven accessions.Result of this experiment has revealed that average mortality rate of callus in 15% PEG treatment is87,64%. HS-49 has shown the lowest percentage rate of response (79%) in 15% PEG treatment,while the highest percentage rate of response occurs for SP-8 (93%). Callus that succeeding growthfrom PEG selection medium will be reproduce in regeneration medium until bud is formed. Buddingconstruct percentage is range between 28,57% (accession HS-49 and SP-38) until 37,03% (accessionSM-35). Average budding construct percentage from selected callus in regeneration medium is31,45%. For the next stage of experiment (second year), those bud will be sub-cultured into rootingmedium until forming root and become complete plantlet ready to acclimatize.